Students’ Attitude toward English Learning: A Study in a Junior High School - -, Lizawati - (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
AbstractStudents? language attitude is one of important things to be successful in language learning process. Student?s attitude is classified into: cognitive, behavior and emotional aspect of attitude. The purpose of this research is to identify students? attitude toward English language learning in a junior high school. This research employed survey research specifically in Junior High School X with 158 students as research participants. The researcher collect the data by using ?Behavior Cognitive Emotional Attitude (BCEA) questionnaire consisting 45 items with five point-likert scale from level 1 to 5. The data were analyzed by using SPSS and Microsoft excel. The findings show that Behavior Aspect of Attitude (BAA) Mean=3.304641; SD=0.815134, Cognitive Aspect of Attitude (CAA) Mean= 3.579747 ; SD=0.829148, Emotional Aspect of Attitude (EAA) Mean: 3.457384 SD: 0.83255 which means students? in Junior High School X have positive attitude toward English learning.Keywords: Students? Attitude, Language Learning, Behavior, Cognitive, Emotional.